Isolation and Characterization of Endophytic Bacteria from The Roots of Avicennia sp. in The Mangrove Area of Gunung Anyar, Surabaya - Fatimah Azzahra; Endang Triwahyu Prasetyawati; Safira Rizka Lestari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Mangroves are unique ecosystems that support biodiversity, including endophytic microorganisms. Endophytic bacteria group is a group of microbes that have a mutualistic symbiosis to the host plant without harming the host, and can act as biocontrol agents and plant stimulants. Endophytic bacteria have a very wide host range. Each plant has an abundance and diversity of endophytic bacteria, depending on the internal and external factors that affect it. This study aims to determine the characteristics of endophytic bacteria and identify the diversity of endophytic bacteria found in Avicennia sp. Method Sampling from mangrove area of Gunung Anyar, Surabaya. Characterization of endophytic bacteria was done by Gram test, spore staining test, catalase test, oxidative-fermentative test, and selective media test (King's B and Yeast Dextrose Carbonate). The results showed the existence of several isolates of endophytic bacteria that have morphological diversity and different characteristics, such as shape, color, colony edge, and colony surface. Conclusions In this study has been successfully isolated some endophytic bacteria such as Lactobacillus sp., Corynebacterium sp., Bacillus sp., Xanthomonas sp., and there are also endophytic bacterial isolates that have not been identified. This study contributes to an early understanding of the diversity of microorganisms in mangrove ecosystems and opens up opportunities for further exploration of their potential applications, one of which is in agriculture